Dynamics of Social Aberrations in Yogmaya’s Sarvartha Yogavani - Neupane, Dipesh (Cognition, 2019)
Yogamaya Neupane is a progressive poet, a spiritual leader, a social reformer, a Nirguna Bhakti saint and a feminist revolutionary in Nepal. She wrote numerous lyrical verses referring to different social evils of her time. This article attempts to explore the dynamics of social aberrations inherent in her lyrical verses –Sarvartha Yogavani. Neupane launches her crusade against different social evils like corruption, deception, racial injustice, caste discrimination, fraudulent activities, misuse of measurement etc. through her sacred verses. Her verses echo the voices of the voiceless people. She is the messiah of contemporary society. Through her verses, she attacks money lenders, corrupt Bhramins, Rana rulers, sellers of crops and Rudrakshya, job holders, judges etc. for their anomalies. She adopts the Bhakti path to launch her social protest against different social aberrations prevalent at that time. The very dynamics of social anomalies of contemporary society are reflected in Yogavani through which she attacks the different social agents against their injustice.